2015
DOI: 10.1039/c5nj00754b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically recoverable chitosan-stabilised copper–iron oxide nanocomposite material as an efficient heterogeneous catalyst for azide–alkyne cycloaddition reactions

Abstract: Chitosan stabilised copper-iron oxide nanocomposite material is found to be a very efficient recyclable/reusable heterogeneous catalyst for azide-alkyne cycloaddition reaction under mild condition. The as-synthesized nanocomposite material is magnetically recoverable and reusable at least up to four times without significant loss in their catalytic activity. The catalytic system is found to be highly useful for the regioselective synthesis of a wide range of 1,2,3-triazoles from various azides and alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…Although the use of chitosan as a carrier to immobilize photosensitizers and catalysts in recent years has been investigated, the studies are mainly focused on the knowledge of the material properties [14][15][16][17][18]21]. Researchers also paid attention to the possibility of using membranes of chitosan or chitosan nanoparticles enriched by photosensitizers for disinfection [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of chitosan as a carrier to immobilize photosensitizers and catalysts in recent years has been investigated, the studies are mainly focused on the knowledge of the material properties [14][15][16][17][18]21]. Researchers also paid attention to the possibility of using membranes of chitosan or chitosan nanoparticles enriched by photosensitizers for disinfection [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For the last years, a new trend of natural polysaccharide bio-polymer -chitosan application as a carrier for photocatalysts and photosensitizers immobilization has been developed [13][14][15][16][17][18][19]21,22]. Although the use of chitosan as a carrier to immobilize photosensitizers and catalysts in recent years has been investigated, the studies are mainly focused on the knowledge of the material properties [14][15][16][17][18]21].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of the efficiency of CuNVPMBA catalyst with that of recently reported polymer‐supported copper catalysts for the click reaction to afford 1,4‐disubstituted 1,2,3‐triazoles is summarized in Table 3. [ 48,49 ] It is noteworthy that the CuNVPMBA catalyst is highly efficient in terms of activity, resistance to oxidation, and stability. The reaction involves the in situ generation of organic azides which are directly converted into 1,2,3‐triazoles.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, SiO 2 with grafted imidazolium cations was proved to be an excellent support, resulting in a stable catalyst that could be used several times under solvent‐free conditions. Biopolymers, such as chitosan, and synthetic polymers decorated with suitable ligands to stabilise the copper catalyst are also suitable supports. However, a noticeable decrease of catalytic activity was observed after the third or fourth run in many cases .…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymers, such as chitosan, and synthetic polymers decorated with suitable ligands to stabilise the copper catalyst are also suitable supports. However, a noticeable decrease of catalytic activity was observed after the third or fourth run in many cases . Excellent results in catalyst recycling were reported with polymers incorporating special organic moieties, such as a tetradentate Schiff base ligand, tris(benzyltriazolylmethyl)amine, (benzimidazoylmethyl)‐bis(pyridylmethyl)amine and dimethylaminomethyl groups, as well as quaternary ammonium or imidazolium ions .…”
Section: Introductionmentioning
confidence: 99%